THE EFFECT OF CHROMIUM ADDITION ON PHYSICAL PROPERTIES OF Cu-Al BASED HIGH TEMPERATURE SHAPE MEMORY ALLOY - Cirak, Z. Deniz; Kok, M.; Aydogdu, Y. (Polska Akad Nauk, Polish Acad Sciences, Inst Metall & Mater Sci Pas, 2018)
Cu-Al-based high temperature shape memory alloys are preferred commonly due to their cheap costs and shape memory properties. In recent years, studies have been conducted on developing and producing a new type of Cu-Al based shape memory alloy. In this study, the CuAl-Cr alloy system, which has never been produced before, is investigated. After production, the SEMEDX measurements were made in order to determine the phases in the Cu84-xAl12Crx+4 (x = 0, 4, 6) (weight %) alloy system; and precipitate phases together with martensite phases were detected in the alloys. The confirmations of these phases were made via x-ray measurements. The same phases were observed by XRD diffractogram of the alloys as well. The values of transformation temperature of alloys were determined with Differential Scanning Calorimetry (DSC) at 20 degrees C/min heating rate. According to the DSC results, the transformation temperature of the alloys varies between 320 degrees C and 350 degrees C. This reveals that the alloys show high temperature shape memory characteristics.
Keywords: Cu-Al based; shape memory alloy; transformation; phase